The Belt and Road Initiative and enterprise green innovation: evidence from Chinese manufacturing enterprises - Cao, Xin; Zhao, Feng; Wang, Yuanyuan; Deng, Yin; Zhang, Heng; Huang, Xiaozhi (Frontiers in Ecology and Evolution, 2023)
Building a green silk road is an important path toward implementation of the UN 2030 sustainable development goals. The purpose of the paper is to discuss the sustainable development goals of the “Belt and Road” Initiative (BRI) by evaluating the relationship between the BRI and enterprise green innovation. Employing the technology–organization–environment (TOE) framework to build a theoretical model based on the micro data of Chinese manufacturing enterprises from 2011 to 2018, and using the difference-in-differences method, this paper analyzes the BRI’s influence on the green innovation of enterprises. The research results indicate that the BRI has significantly enhanced the level of green innovation in Chinese manufacturing enterprises. This effect is still robust after the analysis of PSM-DID excluding the interference of policies in the same period and heterogeneity analysis. The results of the mechanism analysis show that the percentage of R&D employees, policy support and R&D expenditure can enhance the positive effects of the BRI’s influence on enterprise green innovation. The marginal contribution of this paper is to identify the causal relationship between the BRI and green innovation, add a new micro perspective to the research on the relationship between the BRI and sustainable development, and reveal a new micro mechanism.